English Teaching Methodologies of Modern Languages Graduates from a University in Colombia - Carmelina Encarnación Mosquera (Asociación Colombiana de Profesores de Ingles, 2021)
Self-assessment for accreditation purposes requires follow-up of graduates and feedback with academic programs. As part of the improvement actions, this study was done to characterize graduates' methodologies in English language teaching. The data, gathered through questionnaires, showed that graduates privilege the communicative and eclectic methods; the criteria for selecting methodologies are based on their relevance in the teaching context and students' learning needs; furthermore, there is a need and expectation to be updated in methodologies according to the guidelines of the National Bilingual Program. It would be relevant that these results were considered in the curricular development of modern languages and in graduates' professional development activities.